Psychological Vulnerability of Students in General Education School As A Risk Factor for Personal Psychological Health (London Journal of Research In Humanities and Social Sciences, 2024)
The work carried out a situational analysis, assessed the social risks and threats of the educational environment and its negative consequences, which affect the formation of an inferiority complex in children, the emergence of social diseases, the emergence of trends in deviant behavior and problems of social adaptation in the future. The problems of psychological vulnerability of a child in the educational environment of a school are considered, due to the current situation in the education system and the growing needs of society for a psychologically healthy person who could effectively cope with technological, informational and socio-psychological threats of the modern world. The need to create sufficient conditions for the student to ensure such a mental state that makes it possible to master the curriculum well, find a common language with classmates and the teacher, develops his mental and psychological capabilities, contributes to his physical and mental health, and the formation of psychological stability of the individual to the difficulties of life is noted. The importance of developing educational standards, programs, priority technologies for creating a good educational environment at school and the role of psychological services that would contribute to the formation of a healthy and prosperous individual in society are highlighted. The relevance of this problem is also indicated by the fact that it has been studied relatively recently and is not sufficiently developed at the present stage. The theoretical and methodological basis of the study were general scientific methods of analysis, synthesis and generalization of material, qualitative and quantitative assessment of the situation in society. The practical significance and novelty of the article lies in the updating and implementation of new approaches to the formation of psychological health of the individual, in the development of modern mechanisms for the development of a culture of education and psychoanalytic therapy, in the systematization of taking into account the needs of students in secondary schools, the use of methods of universal participation in the decision-making process, partnership activities of teachers and parents, government agencies, social institutions and civil society.
Keywords: Educational environment; risk factor; psychological vulnerability; psychological safety; psychological well-being of the environment; psychological stability.